Estimation of the free energy of hard-sphere crystals via a free-volume approach - Kwak, Sang Kyu (2013)
The free energies of the face-centred (FCC) and base-centred cubic (BCC) hard-sphere (HS) crystals have been estimated via the free-volume approach. We present two free-volume equations for the FCC and BCC HS crystals, which are different from those predicted by Velasco et al. [Langmuir 14(19) (1998), 5652–5655], and the equations exhibit more accuracy than Velasco et al.'s equations. The limitation of using the free-volume approach was assessed by comparing with true free energies obtained by other well-known methods, and possible improvement and application are discussed.